Forensic accounting and fraud examination - Hopwood, William S.; Leiner, Jay J.; Young, George R. (McGraw-Hill, 2012)
Provides fraud's investigation on the market. This title includes a vast range of civil and criminal accounting fraud and related activities, from false business valuations and employer fraud to information security and counter-terrorism.